LED-based Fourier transform spectroscopy of H218O in the 15, 000–16, 000 cm−1 range. (May 2015) - Mikhailenko, S.N.; Serdyukov, V.I.; Sinitsa, L.N.
Abstract: The spectrum of Н2 18 О has been recorded between 15, 000 and 16, 000 cm −1 by a Fourier transform spectrometer with spectral resolutions of 0.03 cm −1 and 0.05 cm −1 using high luminance LED light sources and a 60-cm multipath cell with a path length of 1920 and 3480 cm. A high signal-to-noise ratio ( S/N =10, 000) enabled us to register more than 1500 water vapor lines with intensities 1.0×10 –27 to 2.2×10 −24  cm/molecule at 296 K. 426 rotational-vibrational levels of the H2 18 O molecule were assigned to eleven vibrational states: (014), (033), (052), (113), (132), (151), (212), (231), (311), (330) and (410). 72 Rotational-vibrational levels of the H2 17 O molecule were assigned to six vibrational states: (014), (033), (113), (212), (311) and (410). An extended set of H2 18 O transitions in the 15, 000–16, 000 cm −1 range was generated using the obtained energy level list and the results of a variational intensity calculation. Highlights: The spectrum of H2 18 O was studied between 15, 000 and 16, 000 cm −1 for the first time. 426 Levels of 11 states of H2 18 O were determined. 72 Levels of 6 states of H2 17 O were determined for the first time.